DETERMINACIÓN DE PATRONES DE VARIACIÓN MORFOLÓGICA DEL GÉNERO MINTHOSTACHYS EN UNCHUS y CAJATAMBO, MEDIANTE MÉTODOS ESTADÍSTICOS MULTIVARIANTES DE REDUCCIÓN DE DATOS - Gómez Ticerán, Doris (2008)
The study was conducted in the town of Unchus and in the district of Cajatambo in the departments of Ancash and Lima respectively. Both places are in high Andean territory. The objective of this study was to conduct a comparative analysis of the characterization of gender Minthostachys (muña), from samples collected during the years 2004 and 2005, through graphic representations of the original variables belonging to space R5to R2 using A nalysis Factorial (Jotinson, 2000; Seber, 1984 et al), Principal Component Analysis and Principal Component Analysis Generalised (Flury, 1983; De Paz and Comez, 2002). The morphologyc variables studies were conducted in the Department of Ethnobotany and conomic Botany of the Natural History Museum and the identification of species was conducted in the Herbarium USM using the Classification System Cronquist. The graphics using variables generated by the principal component analysis and Principal Component Analysis Generalised, allow to identify three different species of Minthostachys in communities of Unchus and Cajatambo. The results are confirmed by T2 de Hotelling.